Knowledge and acceptance of influenza and pertussis vaccinations among pregnant women of low socioeconomic status in Turkey - Nurhayat Yakut; Sunullah Soysal; Ahmet Soysal; Mustafa Bakir (Taylor & Francis Group, 2020)
Pregnant women and infants are at relatively high risk for influenza- and pertussis-related morbidity and mortality. Vaccination is the most important prevention strategy for both diseases. We evaluated knowledge and acceptance of influenza and pertussis vaccinations among pregnant women. We performed a cross-sectional survey of 465 pregnant women receiving prenatal care at the obstetric outpatient clinic in a tertiary medical center in Turkey between November 2015 and May 2016. We used a questionnaire investigating the knowledge of pertussis and influenza to evaluate potential influences on the acceptance or rejection of pertussis or influenza vaccinations. The acceptance rates of pertussis and influenza vaccinations were 11.2% and 19.8%, respectively. Maternal age, education level, employment status, number of gestations, and gestational age did not affect the rate of acceptance of these vaccinations. On the other hand, pregnant women who had a history of vaccination during their adolescence and in previous pregnancies were significantly more likely to accept pertussis vaccination. Knowledge about the risks of pertussis and influenza diseases for pregnant women and their children has a significant effect on vaccination acceptance. Even in low socioeconomic status groups, a recommendation for vaccinations by the primary obstetrician was significantly predictive of acceptance of both pertussis and influenza vaccination. This study revealed that the acceptance rates of pertussis and influenza vaccination among pregnant women are very low in Turkey. Healthcare worker recommendations and increased awareness about pertussis and influenza morbidity and mortality in pregnant women and infants are essential to improve the rates of vaccination acceptance during pregnancy.